Catch them young – young farmers trigger climate-smart agriculture in Zimbabwe - Bafana, Busani; Hosenally, Nawsheen (Technical Centre for Agricultural and Rural Cooperation, 2019)
The Zimbabwe Farmers Union (ZFU) thinks school children and students should be in the frontline to raise awareness and trigger action against climate change, a major threat to food security in the region.